Public health perspectives on disability epidemiology to ethics and beyond - Lollar, Donald; Andresen, Elena (Springer, 2011)
Public Health Perspectives on Disability Donald J. Lollar, Elena Andresen, editors Traditionally, the public health viewpoint on disability was geared toward primary prevention of disabling conditions or events. More recently, with the movement for disability rights and the emergence of disability studies, the challenge to the field has been to promote positive health outcomes in this underserved community. Such a change in public health culture must start at the educational level, yet training programs have generally been slow in integrating this perspective?with its potential for enriching the field?into their curricula. Public Health Perspectives on Disability meets this challenge with an educational framework for rethinking disability in public health study and practice, and for attaining the competencies that should accompany this knowledge. This reference balances history and epidemiology, scientific advances, advocacy and policy issues, real-world insights, and progressive recommendations, suiting it especially to disability-focused courses, or to add disability-related content to existing public health programs. Each chapter applies awareness and understanding of disabled persons? experience to one of the core curriculum areas, including: ? Health services administration. ? Environmental health science and occupational health. ? Health law and ethics. ? The school as physical setting. ? Maternal, child, and family health. ? Disasters and disability. In Public Health Perspectives on Disability, faculty, researchers, administrators, and students in graduate schools of public health throughout the U.S. will find a worthy classroom text and a robust source of welcome?and much needed change.